Aloysius Archer : Dream Town - Book 3 - Baldacci, David (New York : Grand Central Publishing, 2022)
"Private Investigator and ex-World War II veteran Aloysius Archer heads to Los Angeles, the city where dreams are made and shattered, and is ensnared in a lethal case"--
Keywords: Novels